Effect of rehabilitation exercises in low back flexibility and muscle strength working for men by age (40-45) years - Sami, Luay; Abdul kadhim, Ali (Journal of Physical Education, 2019)
The rehabilitation exercises have an important role in the rehabilitation of injuries and physical qualities and has a direct impact on the flexibility of the spine and muscle strength working on them. To illustrate this effect, these effects should be studied in rehabilitation exercises. The problem of research is the flexibility of the spine and the lack of muscle strength due to pain. The aim of the research was to prepare exercises to increase flexibility and strength of the spine muscles, as well as to recognize the effect of rehabilitation exercises prepared in flexibility and muscle strength. The researcher used the experimental method. The study sample consisted of (12) aged (40-45) years, representing 60% of the population of the research sample of (20) infected, and tests of elasticity of the spine as well as strength tests of the back muscles. The researcher concluded that the rehabilitation exercises in the role of flexibility and muscle strength down to the back, and rehabilitation exercises prepared to increase the levels of mobility and improve flexibility and muscle strength. The researcher recommends the use of these rehabilitation exercises for flexibility and strength in the rehabilitation of joints and muscles in general, which has an impact on flexibility and affective strength, and took the rehabilitation curriculum (8) weeks (3) weekly rehabilitation sessions with a total of (24) rehabilitation sessions, Minimum time and time of difficulty in the curriculum (15-30) minutes